AHLU KITAB MENURUT SAYYID QUTHB DALAM TAFSIR FI ZILAL Al-QUR’AN - Mustakim, Heru (Universitas Muhammadiyah Surakarta, 2016)
The destination that Allah created human being is to whorship to Allah as an instruction and explanation about whorship. Then Allah sent down his Qur’an and delivered his Prophet as conveyars of the role of the Allah and the lost Kitab that has been sent down to Muhammad SAW as the instruction and figure for the moslems people untill the end of time. The meeting among Islam and Christian and Jew has been running since the birth of Islam in Jazeera. The first century of Masehi, in tht meeting the holy Qur’an is a holy book for moslems took its possision as the corrector for the holy books before. Especially the holy book that has been brought by christians, it’s called Al Kitab. The problems about Ahlu Kitab (Jew and Christian) are very important to be explained, because these problems impact to our aqidah, whorship, relationship many kinds of aspect of life for moslems, beside that the meaning of Ahlu Kitab who is Ahlu Kitab is still cuarreled by ulama, especially still cuarreted by ulama, that this kitab is only for Jew and Christian or there is still group out of them that include in them. Sayyid Qutb is controversi Mufassir among moslems and far ikhwaanul Muslimin. Sayyid Qutb is a figure that was loved by Moslems and as an inspirator for them but in another way the thought of Sayyid Qutb was given comment by ulama’ because of trouble understanding the verse of Holy Qur’an, and some deviation in his aqidah, especially about takfir to the people that have different understanding. After his death Sayyid Qutb’s ideology doesn’t lose away and decrease, in other hand it develope more not only in Egypt but spread to all of countries in the world, finally fondamentalist movement appeared. So that the writter wanted to analyze about the Ahlu Kitab depended on Sayyid Qutb’s book, called Tafsir fie dhilail Qur’an to be applied in Indonesia. The research method that used by the writter is analysist description with library research, this research about Sayyid Quthb’s thought which spreaded in many creation of writting that written became the book that written by someone or many other people. Ahlu Kitab depended on Sayyid Quthb are Jew and Christian generally, the meaning of that statement Sayyid Quthb didn’t limit only for Israel scion (Ya’kub) but all of people who have ideologist as Jew and Christian ideologist, so that they are called Jew and Christian. Depended on Sayyid Quthb, Ahlu Kitab are infiedels politheist. Including people that have religion except Ahlu Kitab and the religions except Islam was still considered as infidel untill they believed in Muhammad and Al Qur’an. The research of this thesis is still about describing generally so that it still needs analysis deeply and in detail. In order to make new knowledge that can be guide for moslem in communication among them and not moslems. Tujuan Allah SWT menciptakan manusia adalah untuk menyembah kepada-Nya. Kemudian Allah SWT menurunkan kitab suci al-Quran dan mengutus nabi-Nya sebagai penyampai kabar tentang peran Allah SWT dan Kitab yang hilang yang telah diturunkan kepada Muhammad SAW sebagai instruksi dan gambaran untuk orang-orang muslim sampai akhir zaman. Pertemuan antara Islam, Kristen, dan Yahudi telah berjalan sejak lahirnya Islam di Jazeera pad abad pertama Masehi, al-Qur’an merupakan kitab suci umat Islam berfungsi sebagai penyempurna kitab-kitab sebelumnya. Terutama kitab yang telah dibawa oleh orang-orang Kristen (al-Kitab). Masalah Ahlu Kitab (Yahudi dan Kristen) sangat penting untuk dijelaskan, karena masalah ini berdampak pada aqidah dan berbagai aspek kehidupan umat Islam. Sayyid Qutb adalah seorang Mufassir di kalangan umat Islam, ia merupakan sosok yang sangat dicintai serta sebagai inspirator bagi umat Islam. Akan tetapi, di sisi lain, ia juga sering dikritik oleh para ulama lain, karena dianggap terlalu sulit dalam memahami tafsir-tafsirnya. Setelah kematiannya, ideologi Sayyid Qutb tidak hilang dan menurun, di sisi lain ia lebih berkembang tidak hanya di Mesir tapi menyebar ke semua negara di dunia, akhirnya gerakan fundamentalis muncul. Sehingga penulis ingin menganalisis tentang Ahlu Kitab berdasarkan pada buku Sayyid Qutb, yang disebut Tafsir fi dilalil Qur'an untuk diterapkan di Indonesia. Metode penelitian yang digunakan adalah deskripsi analitik, jenis kepustakaan. Hasil penelitian adalah, bahwa Ahlu Kitab yang berpedoman pada Sayyid Quthb adalah orang Yahudi dan Kristen pada umumnya, artinya Sayyid Quthb tidak membatasi hanya untuk bani Israel (Ya'kub), tetapi semua orang yang memiliki ideologi Yahudi dan Kristen mereka dipanggil Yahudi dan Kristen. Berdasarkan pada Sayyid Quthb, Ahlu Kitab adalah anti politisi. Termasuk orang-orang yang beragama kecuali Ahlu Kitab dan agama-agama kecuali Islam masih dianggap sebagai kafir sampai mereka percaya kepada Muhammad dan al-Qur'an. Penelitian tesis ini masih membahas secara umum sehingga masih memerlukan analisis secara mendalam dan secara rinci. Untuk mendapatkan pengetahuan baru yang bisa menjadi panduan bagi umat Islam dalam berkomunikasi di antara mereka dan dan juga dengan umat non Islam.